2021
DOI: 10.1007/s10010-021-00476-9
|View full text |Cite
|
Sign up to set email alerts
|

First comparison of the electrical properties of two grid emulators for UVRT test against field measurement

Abstract: The technical rules for connecting turbines to the medium, high or extra-high voltage grid in Germany require the certification of the UVRT characteristics of wind turbines. The state-of-art voltage divider-based test equipment, also named UVRT-Container, is well equipped for executing UVRT tests in field. To conduct the UVRT in field the full wind turbine should be already installed. A second option to perform UVRT tests are system level test benches. They enable the testing of the nacelle. The components tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…In addition, the X/R ratio is another critical parameter for the grid impedance. In the FGW TR3, DUTs are required to stably operate at a minimum SCR of 2 and an X/R ratio of at least 3 [7], [39]. Recently, a more stringent requirement has been introduced by AEMO, i.e., the minimum SCR and X/R ratio are reduced to 1.5 and 2, respectively [40].…”
Section: B Synthesis Of Grid Impedancementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the X/R ratio is another critical parameter for the grid impedance. In the FGW TR3, DUTs are required to stably operate at a minimum SCR of 2 and an X/R ratio of at least 3 [7], [39]. Recently, a more stringent requirement has been introduced by AEMO, i.e., the minimum SCR and X/R ratio are reduced to 1.5 and 2, respectively [40].…”
Section: B Synthesis Of Grid Impedancementioning
confidence: 99%
“…Fig. 5(b) shows the time sequence of the voltage-magnitude changes and the impedance variation [7], [43], [44]. Hence, the MFRT test can be realized by shunting multiple impedances [5].…”
Section: E Combination Of Multiple Testing Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of a certification process using a system test bench was investigated in the research project CertBench [7]. In this project the LVRT behavior of a WT on two different test bench setups are compared to field tests [8]. They have shown that the test bench results are comparable to field test results, if proper test setup is followed.…”
Section: Introductionmentioning
confidence: 99%
“…This project achieved the worldwide first wind turbine certification, solely based upon test bench measurements by means of the German FGW TR3 guideline. An overview of the results [28], and some results on MHiL- [29] and PHiL-specific [30] aspects have been published already.…”
Section: Introductionmentioning
confidence: 99%